Persalinan pada Kehamilan dengan Fetal Hidreosefalus - Annisa Uljannah; Afiqah Divaulhaq (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Hydrocephalus is defined as active distension of the brain’s ventricular system, resulting from inadequate flow of cerebrospinal fluid from its site of production to its site of absorption into the systemic circulation. Hydrocephalus can affect anyone at any age; pediatric hydrocephalus affects 1 in 1,000 live births and is the most common cause of brain surgery in young patients. Hydrocephalus is a pathological condition characterized by abnormal accumulation of cerebrospinal fluid (CSF) due to increased production, impaired flow, or reduced absorption. Ventricular enlargement occurs in response to increased CSF volume and can lead to structural damage to the brain parenchyma. This condition can be congenital or acquired. One key point in prenatal diagnosis is the differentiation between fetal hydrocephalus and non-hypertensive ventriculomegaly. The former qualifies for intrauterine treatment with good outcomes. However, the latter can result in either favorable or catastrophic outcomes due to a damaging etiology, as seen in viral infections such as Zika virus. For an accurate diagnosis, fetal MRI is performed to detect brain anomalies, in addition to fetal ultrasound (to detect common complications), karyotype testing, and TORCH testing (toxoplasma, rubella, cytomegalovirus, herpes simplex). Obstetric management of fetal hydrocephalus depends on the gestational age at diagnosis and the presence of other anomalies. Treatment options include termination of pregnancy before the fetus is viable, placement of a ventriculoamniotic shunt, cephalocentesis before delivery, and/or cesarean section.